2015
DOI: 10.5811/westjem.2015.5.25518
|View full text |Cite
|
Sign up to set email alerts
|

How do Medical Societies Select Science for Conference Presentation? How Should They?

Abstract: IntroductionNothing has been published to describe the practices of medical societies in choosing abstracts for presentations at their annual meetings. We surveyed medical societies to determine their practices, and also present a theoretical analysis of the topic.MethodsWe contacted a convenience sample of large U.S. medical conferences, and determined their approach to choosing abstracts. We obtained information from web sites, telephone, and email. Our theoretical analysis compares values-based and empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…The authors explained that international authors may be more likely to misunderstand the medical specialty addressed at a US conference, and therefore inappropriately submit their work. This would lead to more rejections of international abstracts ( Kuczmarski et al, 2015 ). On the other hand, a prior report regarding cardiovascular disease research showed that international collaboration has been increasing, especially in the European Union.…”
Section: Discussionmentioning
confidence: 99%
“…The authors explained that international authors may be more likely to misunderstand the medical specialty addressed at a US conference, and therefore inappropriately submit their work. This would lead to more rejections of international abstracts ( Kuczmarski et al, 2015 ). On the other hand, a prior report regarding cardiovascular disease research showed that international collaboration has been increasing, especially in the European Union.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that based on the mean scores given for each presentation, 17–20% of subjective decisions for acceptance or rejection would have been reversed ( Blackburn & Hakel, 2006 ). Kuczmarski et al surveyed 27 large scientific conferences to evaluate the screening process for conference abstracts to be presented and found that only two (7%) made the scoring process available to submitters and the public ( Kuczmarski, Raja & Pallin, 2015 ). As a follow-up to the survey, they created a comprehensive scoring system that emphasized transparency and objectivity.…”
Section: Discussionmentioning
confidence: 99%
“…This scoring system asks reviewers to provide 0 to 2 points for each of the seven categories that are outlined by general criteria for each grade, as well as specific examples. We suggest that the SSR takes steps to ensure transparency in their scoring process that may result in improved abstract quality ( Kuczmarski, Raja & Pallin, 2015 )…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5 Medical conferences often apply rubrics designed for judging clinical or basic science submissions, which reflect standard hypothesis-testing methods and often use a single subjective Gestalt rating for quality decisions. 6 This may result in the systematic exclusion of studies that employ alternate, but equally rigorous methods, such as research in medical education. Existing scoring systems, commonly designed for biomedical research, may not accurately assess the scope, methods, and types of results commonly reported in medical education research abstracts, which may lead to a disproportionately high rate of rejection of these abstracts.…”
Section: Introductionmentioning
confidence: 99%